A survey on the knowledge and attitude on pharmacovigilance among the pharmacy students of different universities of Dhaka, Bangladesh - Albee, Md. Hamza (BRAC Univeristy, 2017)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016.